Complexation of 3,4-Dialkyl Isoquinolones Semicarbazone and Thiosemicarbazone with Co(II), Ni(II) and Cu(II) - Rai, B.K.; Sharma, Kaushlendra; Singh, A.K. (Asian Journal of Chemistry, 2010)
A series of complexes of Co(II), Ni(II) and Cu(II) with 3-methyl-4-ethyl isoquinolone, semicarbazone and thiosemicarbazone [MEIQSC(HL1) and MEIQTSC(HL2)] 3-methyl-4-propyl isoquinolone semicarbazone and thiosemicarbazone[MPIQSC(HL3) and MPIQTSC(HL4)] 3-ethyl-4-propyl isoquinolone semicarbazone and thiosemicarbawne [EPIQSC(HL5) and EPIQTSC(HL6)] has been synthesized and characterized on the basis of elemental analysis, IR spectra, electronic spectra, magnetic moment data and conductivity measurements. The analytical data of all the complexes indicates, 1 : 2 metal : ligand stoichiometry of the type [M(HL1-6)2] where M = Co(II), Ni(II) and Cu(II). The ligands behaved as binegative tridentate ligands and can coordinate through amine and imine nitrogen and oxygen/ sulphur donor atoms. The complexes were proposed to be octahedral in geometry and the low value of conductivity indicates their non-electrolytic nature.